Penyelesaian Persamaan Diferensial Biasa Menggunakan Metode Runge-Kutta Orde Keempat Paralel dengan Tiga Prosesor - Iman Al Fajri; Hendra Mesra; Jeffry Kusuma (Department of Mathematics, Hasanuddin University, 2021)
This paper presents a derivation of the Runge-Kutta or fourth method with six stages suitable for parallel implementation. Development of a parallel model based on the sparsity structure of the fourth type Runge-Kutta which is divided into three processors. The calculation of the parallel computation model and the sequential model from the accurate side shows that the sequential model is better. However, generally, the parallel method will end the analytic solution by increasing the number of iterations. In terms of execution time, parallel method has advantages over sequential method.